The Perspective of Islamic Law on the Application of the Polluter Pays Principle in Indonesian Environmental Law - Triana, Nita; Izza, Farah Nuril (al-'adalah, 2020)
This study discusses the implementation of the Polluter Pays Principle in Law Number 32 of 2009 regarding Environmental Management and Protection and relates it to Islamic Law. This research is normative juridical research, a study conducted to find legal rules, legal principles, and legal doctrine in order to address legal issues. This research finds that Law Number 32 of 2009 concerning environmental pollution and destruction contains the Polluter Pays Principle which is indicated by the affirmation that compensation does not only cover environmental restoration measures but also includes providing compensation to victims of pollution. The Law also regulates that responsibility for the perpetrators of pollution is instantaneous at the time of the occurrence of adverse action and not necessarily to be associated with an element of error. The application of this principle is in accordance with the Islamic law principles which explicitly state that environmental damage and pollution are included in actions prohibited by Allah. It's only that Islamic law does not specifically regulate the legal sanctions, but leaves it up to government policy (ta'zir).